STANDARISASI PELABELAN LARUTAN PEREAKSI DI LABORATORIUM QUALITY CONTROL MENGGUNAKAN METODE POKA YOKE UNTUK MENGHINDARI PENGGUNAAN LARUTAN KADALUARSA - Bella Budiani; Fajar Permana; Hari Fadlisyah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
GlaxoSmithKline (GSK) is a multinational pharmaceutical company headquartered in Brentford, London, England. GSK has a Quality Control (QC) department which is responsible for ensuring the quality of raw materials, packaging materials and finished products. In its operational activities, QC requires a reagent solution. The use of the reagent solution which is not suitable causes the test results to be doubtful, so the suitability of the components, especially the expiration date, needs to be considered. The effort made to prevent the use of expired reagent solutions in the testing process carried out by the QC department at GSK is to implement one of the tools of lean manufacturing, namely Poka Yoke. The approach model used is the Poka Yoke control. Control is done by adding a colored dot sticker to the label of the reagent solution based on the month it expires.